EDITORIAL COMMENT: Police Research and Digital Leadership - Suprihanto, Eko; Winarno, Hady; Ari Setyawan, Nugroho; Imam Farid, Muhammad; Bagaskara Gunadi Putra, Satrio; Muchtar, Jarot (Proceedings of Police Academy, 2024)
This editorial comment introduces papers by the Indonesian Police Academy (Akpol) cadets at a seminar on digital leadership in policing. The cadets' papers highlight the application of digital leadership across five core policing functions: investigation, community policing, patrol, traffic, and intelligence. The cadets’ papers present innovative uses of digital platforms, such as social media and dedicated applications, to enhance efficiency and effectiveness in crime prevention, investigation, and community engagement. The papers show the growing importance of police research, the INP’s commitment to problem-oriented policing, and the implementation of digital leadership.